Micro-CT analysis of internal structure of sheared textile composite reinforcement. (June 2015) - Barburski, Marcin; Straumit, Ilya; Zhang, Xinwei; Wevers, Martine; Lomov, Stepan V.
Abstract: Simple shear is a deformation mechanism typical for a woven fabric during draping. The mesoscopic internal structure of the fabric differs between the non-deformed state and a sheared state. This paper presents an analysis of the internal structure of woven fabrics in a sheared state based on micro-CT (X-ray micro computed tomography) imaging of the internal structure of woven fabrics in a sheared state. Two methods for the analysis of the fabric geometry are used: automatic mapping of the local fibre directions based of the micro-CT image analysis and manual measurements of the yarns cross section shape, size and middle line coordinate of yarns on the micro-CT images. Changes of the fibre orientations within the yarns and of the yarn geometrical parameters in a carbon fibre twill woven fabric before and after shear deformation are quantified.